Multisensory Approach in Puppetry Training for Visually Impaired Students : The Application of Multisensory Puppetry Arts for Visually Impaired Students Using the Story of "Si Kancil" at Sanggar Baladewa Surabaya - Galuh Ajeng; Subianto Karoso (Jurnal Pendidikan Sendratasik, 2024)
Trainers at Sanggar Baladewa Surabaya use a special strategy to train visually impaired students in the traditional art of puppetry (seni pedalangan). This study aims to: 1) describe the process of applying a multisensory approach in puppetry training for visually impaired students through the story of Si Kancil at Sanggar Baladewa Surabaya, and 2) analyze the application of the multisensory approach in the puppetry performance of visually impaired students through the story of Si Kancil at Sanggar Baladewa Surabaya. The approach applied in this training is multisensory, maximizing the tactile (touch), kinesthetic (movement), and auditory (hearing) senses. The research used a qualitative approach with data collected through field observation, in-depth interviews, and documentation study, then presented in a descriptive-analytical form. The findings indicate that maximizing tactile, kinesthetic, and auditory techniques in both the training and performance stages is a concrete manifestation of the multisensory approach, enabling visually impaired students to comprehend both the theory and practice of puppetry. In conclusion, maximizing tactile, kinesthetic, and auditory techniques in the training and performance of puppetry through the story of Si Kancil at Sanggar Baladewa Surabaya is highly appropriate and consistent with the training strategies adapted by the studio's instructors. This approach not only made it easier for the students to master puppetry but also strengthened their tactile, kinesthetic, and auditory senses and fostered selfconfidence in visually impaired students. Keywords: multisensory approach, puppetry art, visually impaired students, Si Kancil, Sanggar Baladewa Surabaya.